Pengaruh Efikasi Diri Dan Kompetensi Terhadap Kinerja PNS Pada Inspektorat Jenderal Kementerian Desa, Pembangunan Daerah Tertinggal - Larasati, Rahmatia; Murniyati (CV Warnak Johanna Nusantara, 2025)
Human resource development is a major factor in improving organizational performance, especially in the Inspectorate General of the Ministry of Villages, Development of Disadvantaged Regions, showing that employees who have high competence and good self-efficacy tend to be more able to face work challenges, and overall productivity. This study aims to analyze the effect of self-efficacy and competence on employee performance in the Inspectorate General of the Ministry of Villages, Development of Disadvantaged Regions. This study uses data collection methods, one of which is distributing questionnaires to 50 respondents using saturated sampling techniques. Analyzed using the SPSS version 23 program. The results of the t-test show that self-efficacy has a value of 5.580 with a significance of 0.000, and competence has a t-value of 2.718 with a significance of 0.009, both of which are smaller than 0.05, which means that both have a positive and significant effect on employee performance partially. In addition, the results of the regression analysis show that self-efficacy and competence have a positive and significant effect simultaneously on employee performance with an F value of 21.146 and a significance of 0.000.